Our crusade against the island region and its economic and political impact - اكرم, م.م.په‌رێز اكرم عمر (Sulaimani Journal for Humanities, 2025)
The military invasion of the Crusaders to invade the Islamic-East-occupied countries. There were many reasons for this campaign, although religious reasons were the main reasons. In addition, many other reasons, such as political and economic, played an influential role in launching their campaigns for the Islamic East; especially they started their campaigns in the cities of Ruha. They established the Monarchy of Ruha, which is considered the first Monarchy of the Crusaders'. They had a great influence on the power of the Crusaders over the region, both politically، and economically, and the destruction they did in the region caused a lot of damage to the land and the agricultural products of the region, and on the political side, it caused the supremacy of the Crusaders. Because of their expansion in the region، especially after the great struggles of the region, especially after taking advantage of the uneven words that had spread over the region, which is reflected in the conflict and division between the authorities in the region and the lack of a personality who can be the total force Gather the people of the region and stand up against the crusade.
Keywords: The Crusades; Al Jazeera; Economic Impact; Political Impact